α1-Antitrypsin Pittsburgh (Met358 → Arg) Inhibits the Contact Pathway of Intrinsic Coagulation and Alters the Release of Human Neutrophil Elastase during Simulated Extracorporeal Circulation - Wachtfogel, Yanina T; Bischoff, Rainer; Bauer, Ross; Hack, C Erik; Nuijens, Jan H; Kucich, Umberto; Niewiarowski, Stefan; Edmunds, L Henry, Jr; Colman, Robert W (Thrombosis and Haemostasis, 1994)
Cardiopulmonary bypass prolongs bleeding time, increases postoperative blood loss, and triggers activation of plasma proteolytic enzyme systems and blood cells referred to as the “whole body inflammatory response”. Contact of blood with synthetic surfaces leads to qualitative and quantitative alterations in platelets, neutrophils, contact and complement systems. Contact and complement pathway proteins both induce neutrophil activation, a j-antitrypsin Pittsburgh (Met358 → Arg), a mutant of α1-antitrypsin, is a potent inhibitor of plasma kalli-krein and thrombin. We investigated whether this recombinant mutant protein inhibited platelet activation, as well as contact and/or complement-induced neutrophil activation during simulated extracorporeal circulation.Arg358 α1-antitrypsin did not prevent the 34% drop in platelet count at 5 min of recirculation, did not block the 50% decrease in ADP-induced platelet aggregation at 120 min of recirculation, nor inhibit the release of 6.06 α 1.07 µg/ml (3-thromboglobulin at 120 min of recirculation suggesting that the inhibitor had little effect on platelet activation. However, Arg358 α1 arantitrypsin totally blocked kallikrein-Cl-in-hibitor complex formation but not Cl-Cl-inhibitor complex formation. Most importantly, Arg358 α1-antitrypsin decreased the release of 1.11 α 0.16 µg/ml human neutrophil elastase by 43%. The attenuation of neutrophil activation in the absence of an effect on complement activation via the classical pathway, supports the concept that kallikrein is a major mediator of neutrophil degranulation during cardiopulmonary bypass.